Behaviour of Foreign Institutional Investors in India: An Empirical Study - Guru, Anuradha; Parikh, Anokhi (Indian Journal of Finance, 2009)
This paper studies the dynamics of FII flows and NSE stock returns in India, during the period 2003-2008. The results of the Granger Causality test and Vector Autoregressive model have confirmed the presence of a significant bi-directional causal relationship between scaled FII flows and the NSE stock returns for this period. The impulse response function revealed that the effect of a shock in returns on FII flows was more significant than the effect of FII flows on stock returns. We further examined this relationship before (January 2003 to October 2007) and during the sub-prime crisis (November 2007 to December 2008). We found a uni-directional causal relationship during the crisis, where we find an effect of stock returns on FII flows but not vice versa. Our study supports the base broadening hypothesis, which suggests that increased FII participation, would, with other things remaining constant, lead to a permanent reduction in risk premia and hence, a permanent increase in prices. We also find that FIIs are following positive feedback trading strategies. Our tests reject the price pressure hypothesis which suggests that the rise in prices associated with increase in FII inflows are due to temporary illiquidity and thus, these inflow induced price increases would subsequently be reversed. There is no significant difference in the way FIIs tended to behave before and during the sub-prime crisis.